2018
DOI: 10.1108/jima-02-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of halal purchasing intentions: evidences from UK

Abstract: Purpose This study aims to explore the perceptions of Arabian Muslim consumers about halal food products and to investigate their behaviour towards halal-labelled food products in UK mainstream supermarkets using the theory of planned behaviour (TPB). The role of Islamic religiosity and consumers’ confidence regarding the halal logo as moderating factors is investigated. Design/methodology/approach Cross-sectional data were collected through distributed 400 questionnaires in Scotland, mainly to Muslim consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
135
4
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(169 citation statements)
references
References 53 publications
19
135
4
11
Order By: Relevance
“…Kotler and Keller states that purchasing intentions are consumer actions driven by internal and external factors that ultimately influence consumer decisions in making purchases based on personality traits and consumer decision-making processes [20]. Reham I. Elseidi's study that found that Muslim consumer's desire to buy halal-labeled products from supermarkets in the UK is determined by a positive attitude and a direct consumer attitude [21]. This is in line with the findings of Lada, et al who found that subjective norms were positively and significantly related to the intentions of Arabian Muslim consumers to buy halal labeled foods [13].…”
Section: F Purchase Intentionmentioning
confidence: 99%
“…Kotler and Keller states that purchasing intentions are consumer actions driven by internal and external factors that ultimately influence consumer decisions in making purchases based on personality traits and consumer decision-making processes [20]. Reham I. Elseidi's study that found that Muslim consumer's desire to buy halal-labeled products from supermarkets in the UK is determined by a positive attitude and a direct consumer attitude [21]. This is in line with the findings of Lada, et al who found that subjective norms were positively and significantly related to the intentions of Arabian Muslim consumers to buy halal labeled foods [13].…”
Section: F Purchase Intentionmentioning
confidence: 99%
“…Terkait dengan faktor personal, keputusan pembelian dipengaruhi langsung oleh variabel norma subjektif yang juga dipengaruhi oleh variabel antara yaitu keyakinan atas produk halal (Omar, et al, 2012), juga disarankan untuk memperkuat faktor personal seperti kepercayaan, juga dorongan sosial masyarakat (Alam & Sayuti, 2011), hasil ini juga konsisten dengan hasil studi yang dilakukan di China terkait bagaimana faktor personal mempengaruhi minat pembelian produk daging halal (Afzaal, et al, 2017). Riset lainnya yang dilakukan di Inggris menambahkan spiritualitas atau religiusitas konsumen berpengaruh terhadap minat beli dimana logo halal digunakan sebagai moderating variable (Elseidi, 2017). Penelitian tersebut dilakukan dengan menggunakan sudut pandang Teori Perilaku Terencana dengan studi di Malaysia, studi serupa juga dilakukan di Indonesia terkait dengan upaya pemasaran menggunakan labelisasi halal terhadap minat beli konsumen.…”
Section: Pendahuluanunclassified
“…Dalam tataran epistemologis riset ini memberikan sebuah gambaran terbatas terkait pencantuman label halal pada produk elektronik dan pengaruhnya kepada konsumen. Lebih jauh model kausalitas yang dibangun serta variabel yang masuk ke dalam model riset ini masih sangat sederhana, dan terbuka peluang untuk desain riset ke depan yang dapat memasukkan lebih banyak variabel seperti faktor personal (Omar et al, 2012;Afzaal, 2017 ;Elseidi, 2017), dan faktor sosial (Alam & Sayuti, 2011).…”
Section: Simpulanunclassified
“…Many researches in Muslim consumer behavior, buying intention, and attitude are dominated by Malaysian and Malaysia-based research [1,26,52,53]. Consumer behavior, attitude and intention are shaped by many factors [2,15,19,22], thus it should not be acceptable to assume that Muslim consumers are a homogenous group. Indonesia's potential as a big halal market, Muslim majority population, and gap in halal product consumer research are three main reasons why we chose Indonesia as a study subject in this research.…”
Section: Introductionmentioning
confidence: 99%
“…This study proposes that religiosity and decision-making style influence consumer attitudes toward halal PCP. Many studies show that Muslim attitudes toward halal food products are strongly affected by one's religiosity [15,37] because these products are marketed to cater to specific needs of Islamic religious affiliations. Regardless of whether the products are PCPs or food products, products that carry the halal label are subsequently seen as religiously approved products.…”
Section: Introductionmentioning
confidence: 99%